A novel serial structure repetitive control strategy for shunt active power filter. Issue 1 (7th January 2019) - Chen, Dongdong; Chen, Hao; Hu, Yaowei; Chen, Guozhu
Abstract : Purpose: The purpose of this paper is to propose a novel serial structure repetitive control scheme for shunt active power filter (SAPF) to improve the steady-state accuracy and dynamic performance of SAPF. The novelty of this scheme lies in the reconfiguration of the pole of repetitive control internal model, so that the dynamic response of the repetitive control is improved greatly. Design/methodology/approach: By analyzing the mathematical model of repetitive control, the repetitive control delay can reduce by giving up the needless poles of the internal model, and the general mk + i repetitive control can be designed through the pole configuration method. The controller can track a set of specific order harmonics. Findings: The experimental results are coincident with the theoretical analyses, which prove the effectiveness of the proposed method on harmonic suppression and great performance in dynamic response. Practical implications: An APF prototype has been designed with the serial structure repetitive control proposed in this paper, and it can successfully eliminate the harmonics current of nonlinear load with faster dynamic response. Moreover, the proposed controller can be applied to any three-phase system for fast dynamic response and high tracking accuracy. Originality/value: In this paper, the mathematical model of the repetitive control for specific set of harmonica is developed. A novel serial structure repetitive control is designed, so that the SAPF can eliminate the fundamental reactive current and specific order harmonics and speed up the dynamic response of the repetitive control.